2021
DOI: 10.3389/fmolb.2021.676187
|View full text |Cite
|
Sign up to set email alerts
|

Selective Neuron Vulnerability in Common and Rare Diseases—Mitochondria in the Focus

Abstract: Mitochondrial dysfunction is a central feature of neurodegeneration within the central and peripheral nervous system, highlighting a strong dependence on proper mitochondrial function of neurons with especially high energy consumptions. The fitness of mitochondria critically depends on preservation of distinct processes, including the maintenance of their own genome, mitochondrial dynamics, quality control, and Ca2+ handling. These processes appear to be differently affected in common neurodegenerative disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 441 publications
(501 reference statements)
0
11
0
Order By: Relevance
“…The memory loss and cognitive decline characteristic of AD are caused by atrophy of the entorhinal cortex (EC), mainly of neurons in layer II (ECII), and hippocampus, particularly the CA1 region [ 72 ]. Research has shown that neurons in these areas have high energetic demands and are very sensitive to decreased oxygen and glucose supply [ 263 ].…”
Section: Selective Neuron Vulnerability In Neurodegenerative Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…The memory loss and cognitive decline characteristic of AD are caused by atrophy of the entorhinal cortex (EC), mainly of neurons in layer II (ECII), and hippocampus, particularly the CA1 region [ 72 ]. Research has shown that neurons in these areas have high energetic demands and are very sensitive to decreased oxygen and glucose supply [ 263 ].…”
Section: Selective Neuron Vulnerability In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The pathological hallmark of ALS is degeneration of upper and lower motor neurons, which both have very long axons and, thus, depend on proper mitochondrial function and trafficking [ 72 ]. The large motor unit size imposes high energetic demands on spinal motor neurons to maintain neurotransmission and muscle contraction [ 276 ].…”
Section: Selective Neuron Vulnerability In Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Undoubtedly, neurogenesis is a highly energyconsuming process that requires healthy mitochondria. Mitochondrial abnormalities, together with synaptic degeneration, are the earliest and most prominent features of vulnerable neurons in the brain of AD patients [33][34][35]. For a decade, we have researched the role of mitochondria in the AD-affected brain using mitochondria-targeted antioxidant SkQ1 [31,32,36].…”
Section: Age-dependent Changes In the Density Of Neuronal Progenitor ...mentioning
confidence: 99%